Quality Control Of Capsule A Products Using Statistical Process Control (SPC) And Fuzzy Failure Mode And Effect Analysis (F-FMEA) Methods At PT.LP - Sherin Ramadhania; Dinanjar Husni Mubarok; Mislan Mislan; Asep Rahmatullah; Bambang Setyo Panulisan; Dedy Khaerudin (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2024)
LP is one of the pharmaceutical companies located in Serang, Banten. The production of the company is tablets, capsules, and syrup. Problems that occur at PT. LP is a product defect that occurs in capsule filling, especially in capsule A. The purpose of this study is to determine the defective products that occur in capsule A and to find out the proposed improvements that will be made to reduce product defects in capsule A. The research methods used are Statistical Process Control (SPC) and Fuzzy Failure Mode and Effect Analysis (F-FMEA). The population and samples used were defective capsule A during the production process from March 2022 to May 2023, with sampling techniques through production data, observation and interviews. And the results of research using a check sheet show that the percentage of defects reaches 6%, based on the pareto chart, the priority of improvement that needs to be done is for the dominant type of defect, namely the dented capsule reject reaches 90%, and on the control chart there are still control points that are outside the UCL and LCL. FMEA calculations, the RPN value of the capsule is dented on the head of the capsule or capsule body reaches 384, and the FRPN value is 6.76.